2022
DOI: 10.1101/2022.04.06.487011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery and Visualization of Age-dependent Patterns in the Diurnal Transcriptome of Drosophila

Abstract: Many critical life processes are regulated by input from 24-hour external light/dark cycles, such as metabolism, cellular homeostasis, and detoxification. The circadian clock, which helps coordinate the response to these diurnal light/dark cycles, remains rhythmic across lifespan; however, rhythmic transcript expression is altered during normal aging. To better understand how aging impacts diurnal expression, we present an improved Fourier-based method for detecting and visualizing rhythmicity that is based on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…GSH plays critical roles in protecting cells from oxidative damage and maintaining redox homeostasis. It has been reported that transcription and activity of GSH-producing enzymes increase in aged flies (Klichko et al, 2015;Sebastian et al, 2022); therefore, it is tempting to speculate that glutamate may be diverted into GSH synthesis away from its other roles. However, we found that glutamate supplementation did not increase lifespan under blue light.…”
Section: Discussionmentioning
confidence: 99%
“…GSH plays critical roles in protecting cells from oxidative damage and maintaining redox homeostasis. It has been reported that transcription and activity of GSH-producing enzymes increase in aged flies (Klichko et al, 2015;Sebastian et al, 2022); therefore, it is tempting to speculate that glutamate may be diverted into GSH synthesis away from its other roles. However, we found that glutamate supplementation did not increase lifespan under blue light.…”
Section: Discussionmentioning
confidence: 99%